PERBANDINGAN PENYANGATAN LIEN PADA CT ABDOMEN DENGAN PEMBERIAN BAHAN KONTRAS NON IONIK 300 mgI/ml DOSIS TETAP 80 ml DAN DOSIS 1 ml/kgBB - Cahyawati, TRIANA DYAH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Background. Most abdominal CT is done by using intravenous non-ionic iodine contrast media. Contrast media usage can cause mild, moderate or severe side effects. Contrast induced nephropathy (CIN) is a common cause of death after injection of contrast media. The risk of CIN can be minimized by reducing the volume of contrast media administration. Abdominal CT procedure in Dr. Sardjito Central General Hospital applies 80 ml of 300 mgI/ml nonionic iodine contrast media, for various patient's weight. To reduce the volume of contrast media, the dose should be adjusted based on body weight, without reducing the image quality. Spleen is one of the abominal organs which enhances with contrast media administration. The aim of this study is to determine the differences of splenic enhancement after administration of fixed dose (80 ml) and an adjusted dose (1 ml/kgbodyweight) nonionic contrast media 300 mgI/ml. Subject and Method. This study was an analytic observational with crosssectional study design. The study was conducted in Radiology Department of Dr. Sardjito Central General Hospital. There were 66 subjects divided into two groups: 33 subjects received fixed doses of contrast media (80 ml) and 33 subjects received adjusted dose based on body weight (1 ml/kg). Splenic density measured on abdominal CT, before and after contrast media administration. The difference of splenic enhancement over baseline in each group was statistically analized using Independent T test or Mann-Whitney test. Statistically significance was accepted at p < 0.05. Result. The mean increase in splenic enhancement on the portal venous phase compared to the baseline in the group that received iopamidol 300 mgI/ml with a fixed dose 80 ml was 64,17 HU (SD Â±15,81), and in the group received iopamidol 300 mgI/ml based on body weight (1 ml/kg) was 46,06 HU (SD Â±15,81), with p value <0,05. Conclusion. This study found that splenic enhancement on the portal venous phase in the subjects who received iopamidol 300 mgI/ml with a fixed dose 80 ml was higher than the subjects who received iopamidol 300 mgI/ml based on body weight (1 ml/kg), which was statistically significant (p<0,05).